Rancangan Aplikasi Penjualan Berbasis Web Dengan Metode Prototype - Naufal Farid; Tata Sutabri (Fakultas Teknik Universitas Cenderawasih, 2024)
The rapid development of information and communication technology has encouraged companies to switch to digital platforms in managing their sales. One of the most widely used solutions is a web-based sales application, which allows buying and selling transactions to be carried out online, improving operational efficiency, and expanding market reach. In this study, a web-based sales application was designed using a prototype methodology. This methodology was chosen because of its ability to actively involve users in the development process, through an iterative cycle that allows for direct feedback from users to improve and improve the system gradually. The first step in this design is to collect needs from users or stakeholders through interviews and observations. Based on these needs, an initial prototype of the application was built that included key features such as product management, shopping cart, and payment processing. The prototype is then evaluated by the user, and the feedback is used to refine and refine the prototype until the final application is ready for further development. The resulting app has a full range of features that include product management, a secure checkout system, payment method integration, and real-time sales reporting. The prototype methodology allows developers to detect and resolve potential issues from the early stages of development, thereby minimizing the risk of errors in complex feature implementations. Additionally, the active participation of users in the development process ensures that the resulting application is more in line with the needs and expectations of users. The results of this study show that a prototype-based approach can improve the effectiveness and quality of web-based sales applications, as well as maximize user satisfaction. This application is expected to help companies manage sales transactions more efficiently and expand business reach through digital platforms.